Management Concepts & Practices - Hannagan, T. J.; Bennett, Roger (London : Pitman, 1995)
Managers face increasingly rapid changes in the technology, culture and environment in which they work. This book analyses the challenges and rewards facing managers in terms of theory and practice in all areas of management.
Includes bibliographical references and index.
Keywords: Management; Business and Management